2018
DOI: 10.33275/1727-7485.16.2017.72
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Functional Fеatures of Deschampsia Antarctica (Poaceae) Leaf Blade Growing on the Argentine Islands

Abstract: The objective of the work was to perform the comparative studies of the anatomical structure and reactive oxygen species (ROS) content in leaves of Deschampsia antarctica plants growing in extreme climatic conditions of Antarctica (Skua and Galindez Іslands). The leaf anatomy and surface ultrastructure were investigated by the methods of light and scanning electron microscopy. To determine the localization of monolignines a cytochemical method of dyeing tissues was used. The ROS content was registered by measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…An increase in lignin, cellulose, and hemicellulose content was also observed in poplar seedlings and monocots with a decrease in air temperature [114,115]. The presence of two monolignins (syringyl and guajacyl) in D. antarctica leaf cell walls was revealed (Figure 7c-e) using cytochemical methods and confocal microscopy [109]. The study showed that the content of syringyl and guajacyl in the walls of the adaxial and abaxial epidermis was different, with the highest content of syringyl in the periclinal walls of the upper epidermis and the highest content of guajacyl in the inner walls of both epidermis, the walls of the mesophyll, and conducting bundles.…”
Section: The Influence Of Cold On Leaf Ligninmentioning
confidence: 69%
See 2 more Smart Citations
“…An increase in lignin, cellulose, and hemicellulose content was also observed in poplar seedlings and monocots with a decrease in air temperature [114,115]. The presence of two monolignins (syringyl and guajacyl) in D. antarctica leaf cell walls was revealed (Figure 7c-e) using cytochemical methods and confocal microscopy [109]. The study showed that the content of syringyl and guajacyl in the walls of the adaxial and abaxial epidermis was different, with the highest content of syringyl in the periclinal walls of the upper epidermis and the highest content of guajacyl in the inner walls of both epidermis, the walls of the mesophyll, and conducting bundles.…”
Section: The Influence Of Cold On Leaf Ligninmentioning
confidence: 69%
“…The epidermis of leaves of D. antarctica plants collected on the islands Scua and Galindez characterized the next ultrastructural signs. Oval cells of the adaxial epidermis were covered with an even, smooth cuticle layer (Figure 7a and b) [109]. It was shown that leaf blades were downy.…”
Section: The Influence Of Cold On Leaf Ligninmentioning
confidence: 98%
See 1 more Smart Citation